Kesulitan Belajar Pembelajaran IPS Mahasiswa Prodi Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan UIN Alauddin Makassar - Mega Sulastri; Usman; Umar Sulaiman (Prodi PGMI IAI Sahid, 2023)
This thesis discusses the learning difficulties experienced by students in Social Studies Learning. The aims of this study were to: 1) describe the form of learning difficulties in social studies learning for students of the PGMI Study Program, 2) and describe the inhibiting factors for learning social studies learning for students in the PGMI Faculty of Tarbiyah and Teacher Training UIN Alauddin Makassar. This type of research is descriptive qualitative with research approaches used are pedagogic and sociological. The data sources for this study were PGMI students 3 and 4 class 2017. Furthermore, the instruments used in data collection were interview guidelines, recordings and documentation. The results of this study indicate that the form of student learning difficulties, namely the understanding or cognitive domain of students regarding social studies learning, is more due to students' lack of repetition in learning so that they are less able to master learning and as a result only some of the material is understood by students. While the factors that affect learning difficulties are (1) lack of interest in social studies learning, because during high school / MA students take more science majors than social studies (2) lack of concentration because learning is carried out during the day (3) and lack of subject matter by students to social studies learning. Research implications 1) for students, especially students of the PGMI Study Program should increase motivation to study hard and pay attention to the learning delivered by lecturers, 2) for majors or lecturers, to overcome the forms and factors of student learning difficulties, namely in order to facilitate or complement the needs of students in implementing during the lecture process 3) for further researchers this research can be used as study material so that it can be used as comparison material for further research.